Poly[hydroxybutyrate-co-hydroxyvalerate] and cellulose biocomposite membrane derived from sugarcane bagasse for Congo red dye and vegetable oil removal in water remediation - Aophat Choonut; Alissara Reungsang (PLoS ONE, 2025)
Environmental contamination from textile dyes and oil residues poses a critical environmental and public health concern, highlighting the need for sustainable wastewater treatment strategies. A biocomposite membrane (BM) for the removal of Congo Red (CR) dye and vegetable oil (VO) from aqueous solutions was developed and evaluated separately for each pollutant in this study. Through a solvent casting technique, cellulose fibers (CF) from sugarcane bagasse (SCB) were successfully incorporated into a poly[hydroxybutyrate-co-hydroxyvalerate] (PHBV) matrix, as confirmed by FT-IR and SEM analyses. Exceptional adsorption efficiency was demonstrated by the BM, with 83.79% of CR dye (10 mg/L, pH 6.7) removed within 28,800 s and 95.15% of VO removed within 3,600 s, corresponding to a maximum oil adsorption capacity of 3.11 g-oil/g-sorbent, i.e., more than three times its own VO adsorption on the BM weight. The membrane exhibited good reusability, maintaining over 40% adsorption efficiency for CR dye after three cycles and over 50% efficiency for VO after five cycles. CR adsorption was found to follow the Langmuir model (R² = 0.9869) in isotherm studies, while VO adsorption aligned with the Freundlich model (R² = 0.9784). In kinetic analyses, CR adsorption was best described by the intra-particle diffusion model (R² = 0.9363), whereas VO adsorption followed the pseudo-second-order model (R² = 0.9999). The BM’s performance remained stable in the presence of ionic salts and synthetic wastewater. The significant potential of the BM as an environmentally friendly, cost-effective, and sustainable solution for long-term wastewater treatment applications through simultaneous dye and oil removal is highlighted by these findings.